Acute renal infarction in Turkey: a review of 121 cases - Eren, Necmi; Gungor, Ozkan; Kocyigit, Ismail; Guzel, Fatma Betul; Erken, Ertugrul; Altunoren, Orcun; Turkmen, Aydin (Springer, 2018)
PurposeRenal infarction is a clinical condition which is caused by renal artery occlusion and leads to permanent renal parenchymal damage. In the literature, there are generally case reports on this subject, and few studies that include a large group of patients. Therefore, we aimed to present the data of a large group of patients who were diagnosed with acute renal infarction in our country in this retrospective study.MethodsThe data of patients who were diagnosed with acute renal infarction according to clinical and radiological findings in Turkey in the last 3years were examined. For this purpose, we contacted with more than 40 centers in 7 regions and obtained support from clinically responsible persons. Demographic data of patients, laboratory data at the time of diagnosis, tests performed for etiologic evaluation, given medications, and patients' clinical status during follow-up were obtained from databases and statistical analysis was performed.ResultsOne-hundred and twenty-one patients were included in the study. The mean age was 531.4 (19-91) years. Seventy-one (58.7%) patients were male, 18 (14.9%) had diabetes, 53 (43.8%) had hypertension, 36 (30%) had atrial fibrillation (AF), and 6 had a history of lupus+antiphospholipid syndrome (APS). Forty-five patients had right renal infarction, 50 patients had left renal infarction, and 26 (21.5%) patients had bilateral renal infarction. The examinations for the ethiologies revealed that, 36 patients had thromboemboli due to atrial fibrillation, 10 patients had genetic anomalies leading to thrombosis, 9 patients had trauma, 6 patients had lupus+APS, 2 patients had hematologic diseases, and 1 patient had a substance abuse problem. Fifty-seven (57%) patients had unknown. The mean follow-up period was 14 +/- 2months. The mean creatinine and glomerular filtration rate (GFR) values at 3months were found to be 1.65 +/- 0.16mg/dl and 62 +/- 3ml/min, respectively. The final mean creatinine and GFR values were found to be 1.69 +/- 0.16mg/dl and 62 +/- 3ml/min, respectively.Conclusions Our study is the second largest series published on renal infarction in the literature. More detailed studies are needed to determine the etiological causes of acute renal infarction occurring in patients.
Keywords: Acute kidney injury; Etiology; Renal infarction; Turkey